2008 IEEE Ultrasonics Symposium 2008
DOI: 10.1109/ultsym.2008.0049
|View full text |Cite
|
Sign up to set email alerts
|

Large Qxf product for HBAR using Smart Cut &#x2122; transfer of LiNbO<inf>3</inf> thin layers onto LiNbO<inf>3</inf> substrate

Abstract: In this paper, we propose a novel approach for HBAR devices using the Smart Cut TM technology to obtain thin homogeneous X-cut single crystal films of LiNb03• Sub-micron layers were successfully transferred onto LiNb03 handle wafers.RF characterizations were performed around 1.95 GHz and quality factors in excess of 40 000 are extracted, proving the applicability of layer transfer by Smart Cut TM to acoustic devices. An excellent matching between simulations and experimental data as well as TCF measurements ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The quality factor of the device with only 3 finger electrodes is 3300 at 498.3MHz, yielding a f × Q of 1.6 × 10 12 . This is only one order of magnitude less than the phonon-phonon interaction limited f × Q of bulk LN [22]. Moreover, the k 2 e f f × Q of the device with 5 fingers is 194 where the k 2 ef f and Q are 6.8% and 2850.…”
Section: B Electrode Loading Of Quality Factormentioning
confidence: 89%
“…The quality factor of the device with only 3 finger electrodes is 3300 at 498.3MHz, yielding a f × Q of 1.6 × 10 12 . This is only one order of magnitude less than the phonon-phonon interaction limited f × Q of bulk LN [22]. Moreover, the k 2 e f f × Q of the device with 5 fingers is 194 where the k 2 ef f and Q are 6.8% and 2850.…”
Section: B Electrode Loading Of Quality Factormentioning
confidence: 89%
“…Comparison with other HBAR and BAW resonators. Apart from the GaN/NbN/ SiC epi-HBAR data in this work, our study includes data reported in the literature from solid BAW overtone resonators fabricated from single-crystal bulk quartz, LiNbO 3 , and Si 6,7,17,24,25,42,[60][61][62] , as well as sputter-deposited HBARs on diamond 13,16,20,26,30 , fused silica 14 , quartz 14 , sapphire 5,14,15,21,27,28,63 , silicon 14,15,26,29 , and SiC 16,18,19,26 substrates. The sputter-deposited HBARs use polycrystalline piezoelectric AlN and ZnO thin films deposited on Al, Pt, Mo, and p + doped Si BE.…”
Section: Methodsmentioning
confidence: 99%
“…The overall process is summarized in Fig. 3 and was applied to the transfer of Z-cut LiNbO 3 onto a Z-cut LiNbO 3 wafer [22], of Y-cut LiNbO 3 onto a (100) silicon wafer [7], and more recently to transfer X-cut LiNbO 3 onto X-cut LiNbO 3 [23]. This demonstrates the versatility of the film transfer techniques in providing oriented films, where deposition techniques force the deposition of c−axis-oriented films.…”
Section: B Film Transfer Techniquesmentioning
confidence: 99%
“…To ensure that LiNbO 3 thin films with parallel faces are obtained, Pijolat et al replaced the metal bonding/grinding/polishing approach by a direct oxyde-oxyde bonding and a transfer of the piezoelectric film using the Smart Cut T M process described in section II-B [23]. In this work, the lithium niobate films and substrates were taken as Xcut.…”
Section: B Linbo 3 For Baw Applicationsmentioning
confidence: 99%